Effects of an oxygen-releasing mouthwash for peri-implant health management. A pilot randomized controlled clinical trial - Caroline Paixão CUSTÓDIO; Rubens Moreno de FREITAS; Elcio MARCANTONIO JUNIOR; Rafael Scaf de MOLON; Valdir Gouveia GARCIA (Universidade Estadual Paulista, 2024)
Abstract Introduction The control of peri-implant biofilm plays a crucial role in the long-term success of dental implants. Topical treatment alternatives aimed at reducing or preventing biofilm accumulation around the implant's prosthetic components are critical for the success of the treatment. Objective The present study has clinically evaluated the effects of an oxygen-releasing mouthwash (BlueM®) over a 90-day period, following implant placement surgery. Material and method Inclusion and exclusion criteria allowed for the selection of participants who, after implant placement, were randomized into two groups: the control group, which used a 0.12% chlorhexidine mouthwash, and the BlueM group, which received the oxygen-releasing BlueM mouthwash. All participants were instructed to rinse twice daily for the first 10 days and once a day up to 30 days post-surgery. Clinical parameters were evaluated, including the visible plaque index (VP), marginal bleeding (MB), presence of calculus (PC), suppuration (SUP), mucositis (MU), and the extent of keratinized gingiva (KG). These data were collected at the time of suture removal (baseline). At 90 days postoperative, in addition to the aforementioned parameters, probing depth (PD), bleeding on probing (BOP), and the presence of peri-implantitis (PI) were evaluated. Result Nine patients were included in this study, with a total of 38 implants. The BlueM group demonstrated a reduction in MB and an even greater reduction in VP. The other assessed parameters showed similar results to those in the control group. Conclusion BlueM mouthwash has clinical benefits for biofilm control and gingival inflammation reduction.